Multilayer antireflection coatings model for red emission of silicon for optoelectronic applications - Salih, Kifah Q.; Ahmed, N.M. (Universiti Malaysia Perlis, 2009)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1; issue 1, 2008 & vol. 2; issue 1, 2009.